A to I editing in disease is not fake news - Bajad, Prajakta (RNA Biol, 2017)
Adenosine deaminases acting on RNA (ADARs) are zinc-containing enzymes that deaminate adenosine bases to inosines within dsRNA regions in transcripts. In short, structured dsRNA hairpins individual adenosine bases may be targeted specifically and edited with up to one hundred percent efficiency, leading to the production of alternative protein variants. However, the majority of editing events occur within longer stretches of dsRNA formed by pairing of repetitive sequences. Here, many different adenosine bases are potential targets but editing efficiency is usually much lower. Recent work shows that ADAR-mediated RNA editing is also required to prevent aberrant activation of antiviral innate immune sensors that detect viral dsRNA in the cytoplasm. Missense mutations in the ADAR1 RNA editing enzyme cause a fatal auto-inflammatory disease, Aicardi–Goutières syndrome (AGS) in affected children. In addition RNA editing by ADARs has been observed to increase in many cancers and also can contribute to vascular disease. Thus the role of RNA editing in the progression of various diseases can no longer be ignored. The ability of ADARs to alter the sequence of RNAs has also been used to artificially target model RNAs in vitro and in cells for RNA editing. Potentially this approach may be used to repair genetic defects and to alter genetic information at the RNA level. In this review we focus on the role of ADARs in disease development and progression and on their potential use to artificially modify RNAs in a targeted manner.